Exploring Digital Literary Models in Hypertextual Poetry "Dispossession" by Robert Kendall - Dewi, Marisa Santi (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
Hypertextual poetry is a literary work in digital media with its complexity and uniqueness in accessing and reading it. This study aims to understand the model of digital literature through electronic poetry with the conceptual framework of Cybertext by Espen J. Aarseth (1997). The data collection method used is close reading, while data analysis is by linking text data groups and images in poetry. This study shows some facts about digital literature. (1) "Dispossession" with the hypertextual concept or hyperlink technique restricts access for particular users. (2) The text in the poem is not static and some of the texts have different contents even though they come from the same hyperlink. (3) The reader is not limited by the duration of viewing the poem and the text is impersonal. (4) There is an external link to (the author's website) as well as internal links to (the text of the poem). Those facts show that digital literature provides explorative and interpretative functions for users and readers.